A multivariate analysis of larval fish and paralarval cephalopods assemblages at Great Meteor Seamount - Diekmann, Rabea; Nellen, Walter; Piatkowski, Uwe (Deep Sea Research Part I: Oceanographic Research Papers, 2006)
Assemblage structures and distribution patterns of larval fishes and paralarval cephalopods were examined in September 1998 at Great Meteor Seamount, an isolated seamount located in the subtropical eastern North Atlantic. Early life stages of fish (n=18555) and cephalopods (n=1200) were collected at 23 stations with a multiple opening–closing net, in seven discrete depth strata from 290 m depth (close to the seamount plateau) to the surface. Oceanic species dominated in both taxonomic groups. A peak in diversity was observed at an intermediate depth, in the 100–150 m water layer. Direct and indirect gradient analyses showed distinct species assemblages in the upper and lower part of the water column, separated by approximately 150 m. The division was statistically significant, although a considerable overlap between species was also observed. Above the summit, vertical gaps were found in the distributions of the deeper assemblages, likely caused by increased predation pressure by benthopelagic fish. Horizontal distribution patterns of fish and cephalopods were similar and corresponded to the structure of closed circulation cells detected above the flanks and the flat plateau area. Fish assemblages were significantly different between the inner and outer seamount regime, which was approximately separated by the 1500 m depth contour. Differences in the taxonomic composition of cephalopods were less pronounced; for only one cephalopod species could a direct association with the seamount be assumed. The study indicates a significant retention potential at the seamount that facilitates local recruitment of resident stocks and generates self-sustainable populations isolated from the continental shelf and oceanic islands.